Sustainable subgrade improvement with calcium carbide residue and rice husk ash - Saba Anjum; Abhishek Sharma; Kennedy C. Onyelowe; Abdullah H. Alsabhan; Shamshad Alam; Kanwarpreet Singh; Aditya Kumar Tiwary; Sahil Sharma; Jibran Qadri (Scientific Reports)
Abstract Expansive soils, particularly black cotton soil (BCS), present significant engineering challenges due to their high swelling potential and shrinkage behavior, leading to structural instability. This study evaluates the stabilization potential of calcium carbide residue (CCR) and rice husk ash (RHA) by assessing their combined effects on the geotechnical properties of BCS. Laboratory tests, including differential free swell (DFS), compaction, unconfined compressive strength (UCS), and California bearing ratio (CBR), were conducted to determine the optimal mix proportions. The results indicate that the combination of 10% CCR and 15% RHA significantly enhances soil performance. The DFS index reduces from 73% in untreated soil to 14%, classifying the soil as low-swelling, thereby mitigating its expansive nature. Compaction characteristics improve as the maximum dry density (MDD) increases from 1.551 g/cc to 1.597 g/cc, demonstrating enhanced soil densification and stability. Strength assessments reveal a substantial increase in UCS, attributed to the formation of cementitious compounds from pozzolanic reactions, which enhance particle bonding. The CBR value shows a significant rise from 1.98% in untreated soil to 8.56% with 10% CCR and further to 12.4% with 15% RHA, improving the soil’s load-bearing capacity. Based on these CBR results, the required pavement thickness decreases from 630 mm for untreated soil to 590 mm, highlighting cost and material savings while ensuring structural adequacy. The findings demonstrate that CCR and RHA effectively enhance soil stability, reduce swelling potential, and improve strength, making them viable alternatives for sustainable subgrade stabilization. This research promotes the efficient utilization of industrial and agricultural byproducts while providing a cost-effective solution for geotechnical engineering applications. Finally, the heatmap shows that rice husk ash improves unconfined compressive strength (0.8278), maximum dry density enhances it (0.5239), and excessive optimum moisture content (-0.5) weakens black soil.